The role of internal processes in brand alignment - Harjunpää, Jasmiina (2024)
This thesis investigates the role of internal processes in brand alignment, through a case company, more specifically one of their product family brands. The research focuses on two Market Areas which cover the entire Americas: North, Central and South America. The study investigates the research problem with the help of three research questions, focusing on three areas: level of brand alignment between brand image and brand identity, company's recent name changes and finally, internal processes. To establish a foundation for the study, the theoretical framework walks through the main theoretical concepts: B2B branding, brand identity, brand image, internal brand management, brand alignment as well as the AC4ID Test Framework. This thesis utilizes qualitative research methodology because it is best suited for examining multi-layered topics. More specifically, the research was done by conducting semi-structured interviews with global organization representatives as well as sales personnel from both Market Areas being researched. The thesis concludes that there is brand alignment between brand identity and brand image to some extent. The misalignment stems from two factors: pricing and poor understanding of the portfolio. It can also be seen from the research data that the various company name changes have caused a lack of understanding of offering within the product family brand, its naming and value propositions. Lastly, there was a consensus from all interviewees that the internal communication has been much better recently but there is still room for improvement. The biggest need in internal communication stems from lack of references, which is causing a lack of understanding when it comes to value, benefits and pricing. Also, general brand awareness is lacking in South America. However, in North and Central America it can be stated that brand alignment, therefore brand awareness and understanding is at a good level.